Commentary on “Failer et al. (2022) Developmental endothelial locus-1 protects from hypertension-induced cardiovascular remodeling via immunomodulation” J Clin Invest 2022 (https://doi.org/10.1172/JCI126155) - Markus Sperandio (Pflügers Archiv - European Journal of Physiology, 2022)
Metastatic castration-resistant prostate cancer (mCRPC) remains a leading cause of cancer-related mortality in men. Although poly(ADP-ribose) polymerase inhibitors (PARP inhibitor) are approved for mCRPC patients with homologous recombination repair (HRR) deficiencies, clinical trials combining Olaparib with PD-1/PD-L1 inhibitors have shown limited efficacy in unselected populations. To investigate the immunomodulatory effects of PARP inhibitor in an unbiased manner, we performed bulk RNA sequencing on HRR-proficient MycCaP cells treated with the PARP inhibitor (Olaparib) versus vehicle control. Transcriptomics analysis revealed robust upregulation of CD73 (NT5E), an ectoenzyme and emerging immune checkpoint that generates extracellular adenosine, suggesting an adaptive mechanism that undermines Olaparib efficacy and promotes immunosuppression. CD73 induction by Olaparib was validated in both human and mouse prostate cancer cell lines, with more pronounced effects in HRR-compromised PTEN knockout (KO) cells. Mechanistically, olaparib-driven CD73 expression was mediated through DNA damage-activated ATR-CHEK1-IRF1 and TGF-β1-AKT signaling pathways. In parallel, Olaparib enhanced tumor immunogenicity by activating type I interferon (IFN) signaling and antigen presentation machinery. In vivo, combining olaparib with CD73 blockade significantly delayed tumor growth, improved T-cell infiltration, and augmented CD8⁺ T-cell effector function across HRR-proficient and PTEN KO prostate cancer models. These findings identify Olaparib-induced CD73 upregulation as an adaptive resistance mechanism and support Olaparib plus CD73 blockade as a promising therapeutic strategy for advanced prostate cancer, irrespective of HRR status.